Pemberdayaan Ibu-Ibu Rumah Tangga Melalui Pelatihan Kerajinan Makrame dalam Membuat Benda Fungsional Gantungan Pot - La Diadhan Hukama; Zainal Zawir Simon; Verni Yuliaty Ismail; Efendy Zain (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2018)
This submission activity for society is aimed to give macrame handicraft coaching by making functional productlike vase pendulum from kur rope, nylon rope and the T-shirt yarn. Beside that, forraising the entrepreneurship soul for house wives RT. 08 RW. 05 Kelurahan Cempaka Baru, Central Jakarta.The submission activity method for society is using extracurricular lecture, demonstration, and question answer in making functional product like vase pendulum. This coaching held by lecturers from Management Study Programme Faculty of Economics YARSI University and supported by University students. This activity works with RT. 08 RW. 05 Kelurahan Cempaka Baru, Central Jakarta The result of the submission activity for society is coaching of functional things making like vase pendulum. The coaching runs well. The audience is able to do and make functional things well and they are very enthusiastic to join the coaching from the beginning to the end.